A scoping review of the green parenthood effect on environmental and climate engagement. (23rd January 2023) - Shrum, Trisha R.; Platt, Natalie S.; Markowitz, Ezra; Syropoulos, Stylianos
Abstract: We review the existing literature on the role of parenthood as a motivator of environmental engagement (the green parenthood effect), focusing particularly on climate change. We find that parenthood is severely understudied as a mechanism that may influence climate change‐relevant behavior. The literature on the role of parenthood in driving environmental engagement is mixed, due in part to the role of baseline individual and group characteristics that lead to different impacts of parenthood on environmental engagement as well as to the countervailing impact of intense time and budget constraints imposed by parenthood. Some studies suggest that parenthood increases pro‐environmental engagements, while others find no effects or negative effects. We theorize that potential mediators and moderators need to be taken into account to get a clearer picture of how parenthood influences pro‐environmental engagement. We highlight underlying proposed mechanisms that might be activated during the transition to parenthood (i.e., legacy motives, generativity, perceived responsibility), potential moderators of the green parenthood effect, and insights for public engagement. This article is categorized under: Climate, Nature, and Ethics > Climate Change and Global Justice Perceptions, Behavior, and Communication of Climate Change > Social Amplification/Attenuation of Climate Risks Perceptions, Behavior, and Communication of Climate Change > Behavior Change and Responses The Social Status of Climate Change Knowledge > Climate Science and Social Movements Abstract : Families protest at the COP26 climate summit in Glasgow, Scotland.